Performance assessment of construction companies: A study of factors promoting financial soundness and innovation in the industry - I. M. Horta (2012)
The purpose of the paper is to examine trends in the performance of the Portuguese construction industry, and identify the factors that promote excellence and innovation in the sector. From a methodological perspective, this study enhances the construction of composite indicators using the principles of the "benefit of the doubt" weighting. This involves the use of Data Envelopment Analysis to estimate weights for aggregating the key performance indicators of the construction companies. The paper also proposes a new DEA-based method to assess innovation within an industry, identifying the innovative companies and the extent of innovation. The determinants of good performance and innovation are examined using regression techniques and the statistical significance of the results is ensured by the use of bootstrapping. The study reveals that the Portuguese construction industry experienced a remarkable performance improvement during the 1990s, but this growth trend in performance slowed down in recent years. It is concluded that company performance is strongly affected by the national economic context, and that small specialized companies and large contractors tend to achieve the best performance levels.